1983
DOI: 10.1677/joe.0.0990321
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the prolactin receptor in human prostate

Abstract: The uptake of 125I-labelled human prolactin by subcellular fractions obtained from the human hyperplastic prostate was investigated and the specific binding sites were characterized. The binding was both time- and temperature-dependent with maximum specific uptake achieved after incubation for 20 h at 4 degrees C (dissociation constant = 2.4 x 10(-10) mol/l). The present studies also indicate that the bulk of the specific prolactin binding was confined to the 105 000 and 15 000 g membrane fractions whilst the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Unless speci¬ fied otherwise this particulate membrane fraction was used in all subsequent incubations. Subcellular fractionation of the tissue was per¬ formed according to the method of Leake, Chisholm & Habib (1983).…”
Section: Buffersmentioning
confidence: 99%
“…Unless speci¬ fied otherwise this particulate membrane fraction was used in all subsequent incubations. Subcellular fractionation of the tissue was per¬ formed according to the method of Leake, Chisholm & Habib (1983).…”
Section: Buffersmentioning
confidence: 99%
“…The protein concentration of the final total particulate fraction was adjusted to 1 mg/ml and this was used for all subsequent studies except where indicated otherwise. For experiments designed to determine the subcellular distribution of the specific EGF binding protein, the subcellular fractions were prepared according to the method of Leake, Chisholm & Habib (1983) to provide a crude heavy pellet (800 g), the mitochondrial pellet (15 000 g), the microsomal pellet (105 000 g) and the 105 000 # supernatant fraction (cytosol). Briefly, homogenate samples were incubated with 6-0 nmol/1 (200 000 c.p.m.)…”
Section: Other Chemicalsmentioning
confidence: 99%
“…Pretreatments with MgCl2 and dextran-coated charcoal Membrane suspension was mixed with 2 ml buffer C at room temperature for 10 min as detailed by Leake et al (1983). The membrane suspensions were subse¬ quently centrifuged at the appropriate g force and the resultant pellets reconstituted in buffer A.…”
Section: Other Chemicalsmentioning
confidence: 99%
“…3,12,13 Moreover, patients with prostate cancer have been reported to have higher levels of plasma PRL than did age-matched controls, 3,12,13 and high affinity PRL binding sites have been detected in normal, BPH, and neoplastic human prostate. 3,11,14 PRL, along with growth hormone, belongs to a superfamily of growth factors. 15,16 The peptide hormone is known to have highly pleiotropic actions including those related to regulation of growth and differentiation.…”
mentioning
confidence: 99%